Analisis Persepsi Harga Terhadap Brand Switching Pada Konsumen AMDK Aqua dan Le Minerale - Indah Fitriani; Nungki Agustin; Syamsul Hidayat (Universitas Sains dan Teknologi Komputer, 2024)
This study aims to analyze the effect of price perception on brand switching among consumers of Aqua and Le Minerale bottled water. Research through hypothesis testing, where in the description contains descriptions but the focus lies on the influence between variables. The data analysis method used in this research is quantitative, with SPSS 25 data processing tools. with a sample size of 127 people. The results of hypothesis testing show that the price perception variable has a positive and significant effect on brandswitching of Aqua and Le Minerale bottled water for consumers.